Genesis of accountability and its impact on accounting - Cordelia Onyinyechi Omodero (International Journal of Financial, Accounting, and Management, 2019)
Purpose: This study examines the genesis of accountability: a global view. The concept of accountability has been viewed from various disciplinary lenses in order to develop an integrated understanding of the term. Special attention is devoted to principal—agent perspectives from political science and economics. Research methodology: An integrated framework is developed, based on four central observations. (1) Accountability is relational in nature and is constructed through inter- and intra-organizational relationships. (2) Accountability is complicated by the dual role of nonprofits as both principals and agents in their relationships with other actors. (3) Characteristics of accountability necessarily vary with the type of nonprofit organization being examined. (4) Accountability operates through external as well as internal processes, such that an emphasis on external oversight and control misses other dimensions of accountability essential to nonprofit organizations. Results: The study finds that the time has come for individuals, organizations, stakeholders, establishments, institutions and governments to focus on reporting on their programme results, such as inventory take result and product performance result. Limitation: Paucity of data and empirical works were the major restrictions to this study. Contribution: Thus, being clear about intentions, measuring and understanding results, and making adjustments where necessary, would help assure taxpayers/stakeholders that their money is being spent wisely. A focus on results would also help to ensure that limited public resources are being applied in a way that provides the most value to all concerned. Keywords: Accountability, Genesis, Performance, Responsibility, Types, Assessment, Global